UPAYA PENANGANAN PASIR LAUT DARI SISI KEBIJAKAN - Nurzal, Erry Ricardo (Jurnal Teknologi Lingkungan, 2004)
Sea sand export from Indonesia to Singapore, which is carried out to meet the demand of its coast reclamation, has been predicted to reach 1.8 billion m 3 for the next ten years. Until 2002, reclamation project in Singapore has succeded to finish an increase of its coast with the area of 100 km 2 and the project still needs the sea sand to cover its coast with the area of 160 km 2 . It is predicted that adding the coast surface with the area of 260 km 2 needs 1.8 billion m 3 sea sand. Because Singapore needs the high demand of sea sand, exploitation of the Indonesian sea sand is done execessively which gives adverse impacts to Indonesian coast ecosystem environment. Relating to this, this paper tries to give some recommendations to handle the Indonesian problem of sea sand from the view point of policy.